Low levels of genetic differentiation characterize Australian humpback whale (Megaptera novaeangliae) populations - Schmitt, N.; Double, M.; Jarman, Simon; Gales, N.; Marthick, J.; Polanowski, A.; Scott Baker, C.; Steel, D.; Jenner, K.; Jenner, M.; Gales, R.; Paton, D.; et al. (Wiley-Blackwell Publishing, 2016)
© 2013 Society for Marine Mammalogy. Humpback whales undertake long-distance seasonal migrations between low latitude winter breeding grounds and high latitude summer feeding grounds. We report the first in-depth population genetic study of the humpback whales that migrate to separate winter breeding grounds along the northwestern and northeastern coasts of Australia, but overlap on summer feeding grounds around Antarctica. Weak but significant differentiation between eastern and western Australia was detected across ten microsatellite loci (FST = 0.005, P = 0.001; DEST = 0.031, P = 0.001, n = 364) and mitochondrial control region sequences (FST = 0.017 and FST = 0.069, P = 0.001, n = 364). Bayesian clustering analyses using microsatellite data could not resolve any population structure unless sampling location was provided as a prior. This study supports the emerging evidence that weak genetic differentiation is characteristic among neighboring Southern Hemisphere humpback whale breeding populations. This may be a consequence of relatively high gene flow facilitated by overlapping summer feeding areas in Antarctic waters.